‘SLAPHEDENS’ EPOKE - ET BIDRAG TIL DEN RETROSPEKTIVE (POST-(?)/NEO-(?))MARXISTISKE KRITIK AF IDÉEN OM DET POSTMODERNE BRUD, ELLER: ALT VAR IKKE SPROGSPIL, OG HVOR VAR KAPITALEN, LYOTARD? - Bolt, Mikkel (K&K - Kultur og Klasse, 2014)
THE ERA OF RELAXATION. A CONTRIBUTION TO THE RETROSPECTIVE (POST- (?)/NEO-(?)MARXIST CRITIQUE OF THE IDEA OF A POSTMODERN BREAK, OR; EVERYTHING WAS NOT JUST LANGUAGE GAMES, AND WHERE WAS CAPITAL, LYOTARD? | Through a reading of the development of the philosophy of Jean-François Lyotard the article looks back at the critical revision of Marxism by a generation of French philosophers who were originally affiliated with Marxism themselves but ended up abandoning the Marxist analysis of the capitalist mode of production in favour of a position less critical towards capital.